(3eaGgje CSGSjI aj bhGYO GdHjGfGJs - (3eQGO(B, (3TdHGjIs; (3hGFd CHh eZdj(B, (3fgdI OQhjTs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2000)
(3jMJhj GdcJGH Ydi KeGfjI aUhd gj cGdJGdj ,GdaUd GdGhd (B: (3fXGe eYGdLI GdHjGfGJ (B( (3GdedaGJ (B) . (3GdaUd GdKGfj (B: (3eaGgje bhGYO GdHjGfGJ hgjcdjJgG (B. (3GdaUd GdKGdK (B: (3fehPL GdcjfhfGJ hGdYdGbGJ (B. (3GdaUd GdQGHY (B: (3bhGYO GdHjGfGJ GdYdGFbjI (B. (3GdaUd GdNGeS (B: (3GSJNOGe dZI GdGSJQLGY (B. (3GdaUd GdSGHY (B: (3ebOeI Gdi GcSS (B. (3GdaUd GdKGef (B: (3GdeaGgje GdGSGSjI aj ejcQhShaJ GcSS (B. (3GdaUd GdJGSY (B: (3GdLOGhd (B. (3GdaUd GdYGTQ (B: (3GdYdGbGJ (B. (3GdaUd GdMGOj YTQ (B: (3GdfeGPLs
Keywords: (3GdMGShHs; (3bhGYO GdHjGfGJs